Temperature sensitivity of organic matter decomposition of permafrost-region soils during laboratory incubations. (June 2016) - Bracho, Rosvel; Natali, Susan; Pegoraro, Elaine; Crummer, Kathryn G.; Schädel, Christina; Celis, Gerardo; Hale, Lauren; Wu, Liyou; Yin, Huaqun; Tiedje, James M.; Konstantinidis, Konstantinos T.; Luo, Yiqi; et al.
Abstract: Permafrost soils contain more than 1300 Pg of carbon (C), twice the amount of C in the atmosphere. Temperatures in higher latitudes are increasing, inducing permafrost thaw and subsequent microbial decomposition of previously frozen C, which will most likely feed back to climate warming through release of the greenhouse gases CO2 and CH4 . Understanding the temperature sensitivity (Q10 ) and dynamics of soil organic matter (SOM) decomposition under warming is essential to predict the future state of the climate system. Alaskan tundra soils from the discontinuous permafrost zone were exposed to in situ experimental warming for two consecutive winters, increasing soil temperature by 2.3 °C down to 40 cm in the soil profile. Soils obtained at three depths (0–15, 15–25 and 45–55 cm) from the experimental warming site were incubated under aerobic conditions at 15 °C and 25 °C over 365 days in the laboratory. Carbon fluxes were measured periodically and dynamics of SOM decomposition, C pool sizes, and decay rates were estimated. Q10 was estimated using both a short-term temperature manipulation (Q10-ST ) performed at 14, 100 and 280 days of incubation and via the equal C method (Q10-EC, ratio of time taken for a soil to respire a given amount of C), calculated continuously. At the same time points, functional diversities of the soil microbial communities were monitored for all incubation samples using a microbial functional gene array, GeoChip 5.0. Each array contains over 80, 000 probes targeting microbial functional genes involved in biogeochemical cycling of major nutrients, remediation strategies, pathogenicity and other important environmental functions. Of these, over 20, 000 probes target genes involved in the degradation of varying C substrates and can be used to quantify the relative gene abundances and functional gene diversities related to soil organic matter turnover. The slow decomposing C pool (CS ), which represented close to 95% of total C in the top 25 cm soils, had a higher Q10 than the fast decomposing C pool (CF ) and also dominated the total amount of C released by the end of the incubation. Overall, CS had temperature sensitivities of Q10-ST = 2.55 ± 0.03 and Q10-EC = 2.19 ± 0.13, while the CF had a temperature sensitivity of Q10-EC = 1.16 ± 0.30. In contrast to the 15 °C incubations, the 25 °C microbial communities showed reduced diversities of C-degradation functional genes in the early stage of the incubations. However, as the incubations continued the 25 °C communities more closely paralleled the 15 °C communities with respect to the detection of microbial genes utilized in the degradation of labile to recalcitrant C substrates. Two winter seasons of experimental warming did not affect the dynamics and temperature sensitivity of SOM decomposition or the microbial C-degradation genes during incubation. However, under the projected sustained warming attributable to climate change, we might expect increased contribution of CS to organic matter decomposition. Because of the higher Q10 and the large pool size of CS, increased soil organic matter release under warmer temperatures will contribute towards accelerating climate change. Highlights: Q10 and kinetics of SOM decomposition estimated in incubated permafrost soils. Higher Q10 exhibited by slow than fast decomposing C pools. Decomposition driven by C quantity, quality, temperature and time of incubation. The microbial functional community structure varied with environmental parameters. Increases in Q10 as C was respired was convoyed by shifts in microbial communities.